Development of Learning Media Flash Card Combinations in English Lessons Grade IV MI Al-Huda Karangnongko Sleman - Makarim, Muhammad Fikruzzaman; Haimima, Deana Indah; Iftinan R Azzah S (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study addresses two main questions: (1) how the development process of combination flash card media for English language learning in Grade IV at MI Al-Huda Karangnongko was carried out, and (2) how the appropriateness of the media was evaluated based on expert validation, teacher feedback, and student responses. The research applied a Research and Development (R&D) approach, adapting the Borg and Gall model into eight stages: identifying problems through interviews and observations, conducting needs analysis and literature review, designing the initial prototype, validating with experts, revising the media, conducting limited trials, refining the product, and implementing a large-scale trial. The flash card media was based on Unit I, “What Are You Doing?” from the Grade IV English module published by the Ministry of Education and Culture. The final product consisted of 50 cards (25 vocabulary and 25 picture cards), sized 8 x 12 cm, designed using CorelDraw X7 with attention to visual design and cognitive suitability for elementary students. Validation results showed high feasibility: subject matter experts (93.33%), media experts (92.73%), and instructional experts (93.33%) rated the media as “highly appropriate.” Teachers also gave a positive response (90%), emphasizing the media’s clarity, ease of use, and relevance. A field trial with 26 students showed strong enthusiasm and engagement, scoring 234 out of 260 (90%). In conclusion, the developed flash card media is technically and pedagogically effective, promoting motivation, focus, and understanding in English learning. It offers an innovative alternative aligned with the Merdeka Curriculum’s emphasis on active, enjoyable, and contextual learning.